Essays on the political economy of development - McGuirk, Eoin F. (Trinity College (Dublin, Ireland). Department of Economics, 2013)
The core of this thesis explores three issues at the intersection of political and development economics. In Chapter 2, I demonstrate how ethnic divisions can undermine the provision of an important public good: teacher attendance. In the presence of weak formal institutions- such as those found in many less developed countries -teachers face a lower likelihood of punishment for absenteeism. In these settings, other forms of local collective action are often required to produce public goods and to prevent free-riding. However, a growing literature has shown that local collective action outcomes are often adversely affected by ethnic divisions. I identify the impact of a new measure of ethnic divisions on teacher absenteeism using two datasets: one collected by the World Bank from random unannounced school visits in Uganda, and another collected from over 20,000 respondents to the Afrobarometer survey in 16 sub-Saharan African countries. I incorporate constructivist theories of ethnicity into the measure by allowing the effect of diversity to vary by the salience of ethnic identification in each district. I find that, at high levels of ethnic salience, a one standard deviation increase in ethnic diversity increases the observed absenteeism rate in Uganda by between 3.8 and 9.3 percentage points, or 0.08 and 0.21 standard deviations. In the multi-country survey data, the same change increases perceived absenteeism by 0.08 standard deviations. At low levels of ethnic salience, ethnic diversity has no positive effect on absenteeism in either dataset. I provide suggestive evidence that social capital in the form of within-school teacher networks, rather than community-level monitoring, may explain the findings. The results offer one explanation for why substantial recent investment in education does not seem to be leading to improved test-score outcomes for children in many ethnically diverse countries. The analysis also has implications for the measurement of ethnic divisions …
Keywords: Economics, Ph.D.; Ph.D. Trinity College Dublin.